Oñati Proceedings: The implementation of equal rights for men and women - García Ramos, José Ignacio (dir.) (1991)
Contiene: The implementation ot equal rights for men and women; Successive obstacles to women's rights; Obstacles to the implementation of women rights; Indigenous jurisprudence: Going back in order to go forward; Equality in political participation and decision making; Equal rights for men and women in Japan; The validity and limit of the system of "Common surnames for married couples" in Japan; Implementing th freedom charter in South Africa: Equal rights for women?; Equal rights for men and women in East-European Countries; y otros.